Designing CS Farming Systems towards Carbon-Neutral Sustainable Agriculture in Andhra Pradesh and Telangana, India - Jat, Mangi Lal; Kumar, Yogesh; Kalvaniya, Kailash C.; Rana, Dharamvir Singh (2021)
In the South India region, the inefficient use and mismanagement of production resources, especially land, water, energy and agro-chemicals, have vastly impacted health of the natural resource base resulting into global warming led climatic variability. Several climate-smart agricultural practices (CSAPs) developed, refined and tested by several agencies and research organizations, demonstrated improved productivity, resilience and adaptive capacity for different commodities and agro-ecological zones within the region. However, the perception of farmers on climate vulnerability and responses of the CSAPs vary with bio-physical and socio-economic diversity of farm households. The lack of integration of bio-physical and socio-economic knowledge in technology targeting, limits the large-scale adoption by diaspora of farmers specially marginalized and women farmers. Therefore, development and targeting portfolios of CSAPs require in-depth understanding of the diversity of farming practices, and assessment of various interventions on the adaptive capacity of farming community as well as food security. Designing and applying adapted household survey to understand the diversity of farming systems in each location. The major cropping systems in Andhra Pardesh and Telanana, India are maize-maize and rice-maize where the farmer’s field size is very small comparatively. Conducted meetings and trainings with group of farmers in selected villages through demonstration of different interventions and distributed required implements to small holding farmers, trained them about LCC, GS and MNBS by experts. Also visited progressive farmers’ field and planned about the rabi sowing crop and shared to the data collection sheet and urea calculator.